Revealing students’ social-emotional competence of the English education department - Armanda, Muhamad Laudy; Widyantoro, Agus (LITERA, 2025)
Beyond equipping pedagogical competence, English Education students are increasingly expected to navigate diverse classroom environments, cultivating social and emotional competence (SEC) to confront cultural sensitivity in today’s 21st century. SEC is crucial for pre-service teachers as they prepare to educate future generations. Although extensive research has been carried out on SEC in foreign language learners, no study portrays English Education students’ SEC across programs. Through a quantitative survey research design, this study investigates the perceived levels of English Education students’ SEC and measures to what extent their levels vary according to their gender and education levels. A questionnaire survey of the social-emotional foreign language learning scale (SEFLLS) was distributed to the participants. Descriptive analyses (mean, standard deviation) and inferential statistics (Mann-Whitney U test) were conducted to analyze the data. The significant findings highlighted that English education students have high levels of overall social-emotional competence in both programs. Besides, findings indicated no significant difference based on participants’ gender in their SEC and dimensions. Similarly, no significant differences were found between participants’ education levels regarding their self-regulation and social relations. Yet, a significant difference was detected in the decision-making dimension and overall SEC. Subsequent studies could examine SEC factors across different cultures or socioeconomic levels in the context of language learning.